(untitled) (Research, Society and Development, 2020)
Geography teaching has always faced some difficulties with regard to the study of space, which requires accurate information about places. Part of these difficulties can be minimized with the help of technology. Being indispensable for some geography teaching activities. Innovation in teaching geography is of great importance, there are many subsidies, but it needs a direction, a simple guideline or a base on which it is based, such as changes caused by the insertion of technologies. Thus, this research addresses how geotechnologies (or space technologies) can assist in the teaching-learning process. Adopt a methodology to survey the bibliographic base. And the results obtained demonstrate the importance of inserting technology criteria in the classroom, with the teacher’s primary role as mediator of this process.